THE WATER EXTRACT OF Saragassum fusiforme IS A POTENTIAL ELICITOR OF INDUCED RESISTANCE IN SOLANUM LYCOPERSICUM BUT NOT IN Nicotiana benthamiana - Layth Sbaihat; Daigo Takemoto; Kazuhito Kawakita (International Journal of Biosciences and Biotechnology, 2014)
Molecules called elicitors induce plants’ defense responses.Elicitor -??induced resistance rarely leads tocomplete pathogen control, but reduce lesion size and/or number instead. We investigated a novel elicitorextractedfrom the brown sea algae (Saragassum fusiforme), whichis sowed to induce reactive oxygen speciesproduction and protection against powdery mildew and late blight diseasesoftomato (Solanum lycopersicum,cultivar Lady First)plants. On the other hand, the studied elicitor did not induce reactive oxygen speciesproduction in Nicotiana benthamiana plants nor protected them against late blight disease .